An Analysis of Leading Sectors as an Effort to Develop the Economy of Sidoarjo Regency During the 2019-2023 Period - Hermawan, Mokhammad Setyfani; Bintoro, Nugroho Suryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to determine the leading sectors and shifts in economic sectors as an effort to develop the economy of Sidoarjo Regency. This study uses secondary data in the form of time series from the Gross Regional Domestic Product (GRDP) of Sidoarjo Regency and East Java Province in 2021-2024. The analysis method used in this study uses Location Quotient (LQ) Analysis, Shift-share, Growth Ratio Model (GRM), and Overlay to identify leading sectors and shifts in economic sectors in Sidoarjo Regency in 2019-2023. The results of this research Sidoarjo Regency has three leading sectors, namely the Manufacturing Industry sector; Electricity and Gas Procurement; Transportation and Warehousing and there is a shift in the economic sector, namely the transportation and warehousing sectors have changed and are not competitive, on the other hand the Accommodation and Food and Beverage Provision sector; and Real Estate has competitiveness.